A SOCIOLINGUISTICS STUDY ON LANGUAGE ATTITUDE OF THE SUNDANESE COMMUNITY IN EASTERN PRIANGAN TOWARDS ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Setyo wati (Humanitatis : Journal of Language and Literature, 2019)
A research of language attitude is getting much attention for years in some fields. Due to the importance of the language attitude, this research intends to describe the language attitude of Sundanese towards English language in Eastern Priangan, West Java Province. This study employed a descriptive qualitative research. The data used is the data obtained through questioners, observations, and in-depth interviews to know the attitude of the Sundanese community language. Respondents which were involved in the research are respondents living in Eastern Priangan, such as Ciamis, Banjar, Tasikmalaya city, Tasikmalaya regency, Sumedang, Garut, and Pangandaran. This research took a social situation. The result of the research shows that Sundanese people in Eastern Priangan have different language attitude, in terms of cognitive, behavioural, and affective aspects towards English as a foreign language. It indicates that the language attitudes of Sundanese community have different language attitudes towards English, in terms cognitive, behavioural, and affective aspects. Briefly, most of respondents’ obvious positive language attitude towards English can be concluded that they were well conscious of English importance. The research result reveals the Sundanese respondents have the negative affective attitude towards English. Positive behavioural language attitude of Sundanese community towards English shows lower than Sundanese. It shows that Sundanese people tend to speak Sundanese language than English language. Sundanese people tend to speak their mother tongue since they live in West Java where most people speak Sundanese language.